Sex and body composition influences the Quilombolas strength. Issue 1 (5th December 2020) - Pereira, Leonardo Costa; de Santana, Frederico Santos; Lamarca, Fernando; Garcia, Kerolyn Ramos; Karnikowski, Mauro; Neto, Luiz Sinésio Silva; Oliveira, Hildeamo Bonifacio; Osório, Neila Barbosa; da Silva, Izabel Cristina Rodrigues; de Oliveira Karnikowski, Margo Gomes
Abstract: Background: Studies in ethnic minority communities with social isolation have low genetic variability. Furthermore, assuming that any attempt to determine ageing by chronological cuts is misleading, it is recommended that functional capacity assessments be performed especially during and at the end of adulthood. Specifically, muscle strength performance is an interesting screening measure of functional capacity because of its association with functional level. However, the behaviour of the muscle strength manifestation between sexes and its association with body composition (BC) parameters in a low genetic variability community are unknown. Therefore, the objective of this study was to verify the influence of BC and sex on the handgrip strength of mature remaining Quilombolas. Methods: Seventy Quilombola volunteers of both sexes (♀ = 39; ♂ = 31) were recruited. BC and muscle strength were tested by dual‐energy X‐ray absorptiometry (DEXA) and handgrip equipment (Jamar), respectively. Correlations between muscle strength and age and BC parameters were determined by Spearman equation. In addition, it has executed comparisons of BC and age between strongest and weakest men and women from the interquartile analysis by Mann–Whitney U test. The significance level was adopted: P ≤ 0.05. Results: Of the 70 remaining Quilombolas, with a mean age 64.6 ± 7.07 years, 55.7% were women with a mean age of 63.77 ± 7.56 years and 44.3% men with 65.65 ± 7.87 years. Statistical differences were identified for all parameters of BC and performance evaluated between men and women, except for the ratio of appendicular and axial fat‐free mass ( P = 0.183). The evaluation of the influence of BC on strength identified that Quilombola men and women have different processes in the decline of strength, considering both the correlation's tests and the comparisons between groups of different degrees of strength. Conclusions: For Quilombola individuals, strength is a variable that can be modulated due to the influence of gender and BC.